The Influence of Work Environment, Job Stress, and Job Satisfaction as Intervening Variables on Turnover Intention of Hotel Employees XYZ - Clara Dini Ayunita; Mulatsih Mulatsih; M. Ali Iqbal; Edi Subarkah (Budapest International Research and Critics University, 2022)
This study aims to analyze the factors that influence employee turnover intention at Hotel XYZ. The population of this study is all employees at Hotel XYZ with a total sample of 184 employees with an observation period of 2019-2021. The endogenous variables used are job satisfaction and turnover intention, while the exogenous variables used are work environment and work stress. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The results of the study stated that the work environment and work stress had a positive and significant effect on job satisfaction; the work environment has no effect on turnover intention; work stress has a positive and significant effect on turnover intention; job satisfaction has a significant negative effect on turnover intention; Job satisfaction is able to mediate the relationship between work environment and work stress on turnover intention.